Role of HA1C in early detections of Prediabetic children - SABER A.M. EL-SAYED; RAMI AMIN GASHGARY (International Journal of Pharma and Bio Sciences, 2017)
Diabetes mellitus is a chronic metabolic disease as a result of defect in secretion of insulin or defect in insulin action despite of normal secretion or defect in both secretion and action , diabetes mellitus associated with hyperglycemia and high blood glucose levels , type 1 diabetes mellitus result from mainly immune mediatedor non-immune mediated due to chronic pancreatitis with destruction of β cells of pancreas responsible for its productions , glycosylated hemoglobin is an index of long period of diabetes without control or delayed discover of patients, the diabetic patients need continues care and educated fore self-managements. An early detection of diabetes mellitus among high-risk groups (relative to diabetic children and obese children) by HA1c. Prediabetic occurs because of the interaction between genetic and environmental factors. Our study was performed over 80 children following the Endocrine clinic of the Pediatric Department, of Zagazig general and Healthy Insurance Hospitals in Sharika Egypt, group 1 were 60 children of elevated risk for diabetes (relatives to diabetic children as siblings) 28 males and 32 females their age from 2y to 18y and another group 2 which were 20 children with obesity 8 males and 12 females their age from 3y to 18y, they underwent to full history, clinical examination, detailed measurements (anthropometric), full investigations with estimation of glycosylated hemoglobin (HbA1c) and genetic counseling of the family. As shown of glycosylated hemoglobin no significantly difference were found among our groups of study, at the start of study HA1c Normal range (Ë‚5.7) found in 57 (95%) in group 1 and in 16 (80%) in group 2, Prediabetic range (5.7-6.4) at the start were 2 siblings (3.3%) in group 1 and 2 obese children (10%) then also non-significant after 3 months follow up HA1c% were Prediabetic range (5.7-6.4) after 3 months were (1.7%) in 1 patient of group 1 and were (5%) in 1 obese patient of group 2 and Prediabetic range (5.7-6.4) after 6 months returned normal in group 1 and I obese female (5%) in group 2 The HbA1c test is an early detector of diabetes mellitus among high-risk groups. Prediabetes occurs because of the interaction between genetic and environmental factors. Controlling the environmental factors by proper family counseling can delay and even inhibit the emergence of diabetes.